Taxonomical Studies of Selected Ornamental Plants - Oloyede, F. M.; Illoh, H. C.; Oloyede, F. A. (2014)
The neglect of ornamental horticulture by researchers in Nigeria is now more evident than ever. This might be attributed partly to general lack of interest in ornamental studies and also partly due to plant identification problem. This work is therefore aimed at the collection, identification, description and propagation of eight ornamental plants of Nigeria [Caladium bicolour Wightii, Chrysothemis pulchella (Donn ex Sims) Decne., Coleus blumei Benth, Episcia cupreata (Hook) Hanst, Impatiens balsamina L., Kalanchoe fedtschenkoi Harnet and Perr 'Marginata', Pellaea rotundifolia (G. Forst) Hook and Rhoeo spathacea (discolor) Hance]. The plants were collected in Osun State, Nigeria and identified using standard horticultural literatures and herbarium specimens of the Department of Botany, Obafemi Awolowo University, Ile-Ife, Nigeria. The plants were raised in triplicates at the screen house. Data were collected on growth parameters. Morphological observations showed that the plants were herbaceous and annuals with simple leaf habit. There were variations in the shapes of their apex, base, margin, calyx and petal. The number of their calyx, petal and the leaf arrangement also differ. Reticulate venation was common to them with the exception of C. bicolor and R. spathacea with parallel venation. They possess actinomorphic flowers except I. balsamina with zygomorphic flowers. Almost all the plants studied are propagated by stem cuttings with the exception of I. balsamina, P. rotundifolia and R. spathacea. Their maturity periods range from 25 - 150 days. The need for awareness of the importance of ornamental plants for their values was discussed.